'It's just so much waste.' A qualitative investigation of food waste in a universal free School Breakfast Program. Issue 9 (29th December 2014) - Blondin, Stacy A; Djang, Holly Carmichael; Metayer, Nesly; Anzman-Frasca, Stephanie; Economos, Christina D
Abstract: Objective: To understand stakeholders' perspectives on food waste in a universal free School Breakfast Program implementing a Breakfast in the Classroom model. Design: Semi-structured focus groups and interviews were conducted with school district stakeholders. Inductive methods were used to code resulting transcripts, from which themes were identified. The analysis provides a thematic analysis of stakeholders' perspectives on food waste in the School Breakfast Program. Setting: Ten elementary schools in a large urban school district implementing a universal free Breakfast in the Classroom model of the US national School Breakfast Program. Subjects: Elementary-school students ( n 85), parents ( n 86), teachers ( n 44), cafeteria managers ( n 10) and school principals ( n 10). Results: Stakeholders perceived food waste as a problem and expressed concern regarding the amount of food wasted. Explanations reported for food waste included food-related (palatability and accessibility), child-related (taste preferences and satiation) and programme-related (duration, food service policies, and coordination) factors. Milk and fruit were perceived as foods particularly susceptible to waste. Several food waste mitigation strategies were identified by participants: saving food for later, actively encouraging children's consumption, assisting children with foods during mealtime, increasing staff support, serving smaller portion sizes, and composting and donating uneaten food. Conclusions: Stakeholders recognized food waste as a problem, reported myriad contributing factors, and have considered and employed multiple and diverse mitigation strategies. Changes to the menu and/or implementation logistics, as well as efforts to use leftover food productively, may be possible strategies of reducing waste and improving the School Breakfast Program's economic, environmental and nutritional impact.